How is Development Economics Taught in Developing Countries? - McKenzie, David (Taylor and Francis, 2018)
A survey of instructors and data collected from course syllabi and examinations are used to examine how the subject of development economics is taught at the undergraduate and master's levels in developing countries, compared to undergraduate classes in the United States. Topic coverage, teaching approach, and means of assessment all differ from that in leading U.S. economics departments. Development economics is taught largely as a theoretical subject coupled with case studies in developing countries, with few courses emphasizing use of data or empirical methods. Limited financial resources, the educational level of students, and low involvement of instructors in research are considered as explanations for the way the subject is taught in developing countries. The authors conclude with suggestions for improving teaching of development economics.